Cahills vs. Vespers : day of doom - Baldacci, David (39 clues. Cahills vs. Vespers, 2013)
After delivering the last ransom, Amy and Dan discover that Vesper One has a terrifying plot and they race against time to stop him from harming millions of innocent people.